2004
DOI: 10.1016/j.visres.2003.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Stopping the motion and sleuthing the flash-lag effect: spatial uncertainty is the key to perceptual mislocalization

Abstract: A moving object is perceived to lie beyond a static object presented at the same time at the same retinal location (flash-lag effect or FLE). Some studies report that if the moving stimulus stops moving (flash-terminated condition or FTC) the instant the flash occurs, a FLE does not occur. Other studies, using different stimuli, report that the FLE does, in fact, occur in the FTC. The FTC is thus a crucial turning point in theories of flash-lag. Unraveling the mystery of the FLE in the FTC will help unravel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
102
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 49 publications
17
102
3
Order By: Relevance
“…However, in this experiment we did not find a total elimination of the flash-lag effect; a small but significant forward displacement for blanks of 120 ms was still measured. This effect is likely due to the fact that observers did not foveate the position of the flash, a finding that is consistent with Kanai et al (2004), who reported a flash-lag in the flash-terminated condition for peripherally presented stimuli. In previous pilot studies, where stimuli were presented foveally and the separation between the moving object and the flashes was smaller, observers actually achieved close to perfect localization performance, that is, a total elimination of the flash-lag effect (data not presented).…”
Section: Discussionsupporting
confidence: 82%
“…However, in this experiment we did not find a total elimination of the flash-lag effect; a small but significant forward displacement for blanks of 120 ms was still measured. This effect is likely due to the fact that observers did not foveate the position of the flash, a finding that is consistent with Kanai et al (2004), who reported a flash-lag in the flash-terminated condition for peripherally presented stimuli. In previous pilot studies, where stimuli were presented foveally and the separation between the moving object and the flashes was smaller, observers actually achieved close to perfect localization performance, that is, a total elimination of the flash-lag effect (data not presented).…”
Section: Discussionsupporting
confidence: 82%
“…Conceptually similar models have been proposed by previous investigators to explain related phenomena in retina (Berry et al, 1999), thalamus (Sillito et al, 1994), primary visual cortex (Jancke et al, 1999;Fu et al, 2004), extrastriate cortex (Mikami, 1992;Sundberg et al, 2006), and behavior (McKee and Welch, 1985;Verghese et al, 1999); although implementation details differ, these computational schemes share the underlying notion of what has been termed "asymmetric spread" (Kanai et al, 2004), "priming" (Sheth et al, 2000), "feedforward wave" (Baldo and Caticha, 2005), or "sequential recruitment" (McKee and Welch, 1985). There is overall consensus that this progressive activation of the motion-sensitive circuit, which may be interpreted as a rudimentary extrapolation mechanism (Baldo and Caticha, 2005) or locking/focusing device (Sillito et al, 1994), may be connected to a class of anticipatory perceptual phenomena.…”
Section: Self-reinforcing Feedback Modelmentioning
confidence: 56%
“…Previous studies by Fu et al (2001) and Kanai et al (2006) demonstrated that the extrapolation of visual targets farther in the direction of motion was larger for spatially blurred targets-that is, for targets with a high degree of position uncertainty. Our results at paralateral spatial locations are in accord with these earlier findings and confirm that position uncertainty due to less precise encoding of spatial coordinates leads to larger forward displacements.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in which position uncertainty was induced either by the blurring of target intensity and contrast (Fu, Shen, & Dan, 2001) or by peripheral stimulus presentation (Kanai, Sheth, & Shimojo, 2006) have shown that less accurate positional information results in larger forward displacements. On the basis of the latter findings, we hypothesized that less precise encoding of spatial coordinates in paralateral and lateral space leads to greater position uncertainty and should be reflected in an increase in the magnitude of forward displacement.…”
mentioning
confidence: 99%